Hubungan Antara Gaya Kepemimpinan Transformasional Dengan Kepuasan Kerja Pada Pegawai Non-Medis Rumah Sakit PKU Muhammadiyah Surakarta - Husni, Ikmalia Rahmatin; , Achmad Dwityanto, S.Psi, M.Si (2017)
Job satisfaction is a very important factor in a company or organization. This relates to how companies make employees able to survive in the company and issue his best performance in a work by looking at the rights of employees, especially the problem of relations with the leaders and the amount of remuneration. One of the determinants of job satisfaction is a transformational leadership style, where employees will feel needed by its leaders thereby creating a harmonious relationship and comfortable working conditions. Thus, the job satisfaction can be achieved. The purpose of this study which is to determine the relationship between transformational leadership style and job satisfaction, so the authors propose a hypothetical "There is a positive relationship between transformational leadership style and job satisfaction". Subjects in this study were employees of non-medical Hospital of PKU Muhammadiyah Surakarta totaling 100 people. The sampling technique used is cluster sampling technique, a method where the population is divided into several sub-populations or units. Each subunit is taken the sample members randomly. Measuring instrument used in this study there are two gauges, namely: (1) the scale of transformational leadership style, and (2) job satisfaction scale. Analysis of the data in this study using the product moment correlation. Based on the results of the analysis, the obtained correlation (r) between transformational leadership style and job satisfaction of 0.635 with a significance of 0.000 (p <0.01). It shows there is a significant positive relationship between transformational leadership style and job satisfaction. That is, the higher perceptions of transformational leadership style eating the higher the job satisfaction of employees, conversely the lower perceptions of transformational leadership style will also lower the job satisfaction of employees. Average empirical variables of transformational leadership style with a mean hypothetical (RE>RH) which describes non-medical employees of PKU Muhammadiyah Hospital in Surakarta own perceptions of transformational leadership style is high. Furthermore, the empirical mean of job satisfaction variables with a mean hypothetical amount of (RE>RH), which means non-medical employees of PKU Muhammadiyah Hospital in Solo have high levels of job satisfaction. The role of transformational leadership style on job satisfaction is at 40.3%, which means that there are 59.7% that affect job satisfaction, for example, among others: the work environment, work in a team, benefits, and much more. Keywords: Transformational Leadership Style, Job Satisfaction.